2017
DOI: 10.2340/00015555-2574
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Senile Pruritus: From Diagnosis to Treatment

Abstract: Pruritus occurs frequently in the elderly population, but it has not been fully defined and its precise prevalence is unknown. Putative causes of pruritus are numerous and patients' quality of life can be greatly reduced. In the absence of any specific cause, a diagnosis of senile pruritus is proposed, suggesting that itch is secondary to ageing. However, the relationship of pruritus with skin ageing and/or neuronal ageing and/or immune ageing is poorly understood. Many treatments have been reported, but are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 55 publications
(115 reference statements)
3
27
0
3
Order By: Relevance
“…In this study, senile pruritus patients had significantly higher TEWL values than control subjects (13.13 ± 4.28 versus 6.71 ± 2.45, p < 0.01; Table 3). These results suggest that senile pruritus is associated with dysfunction of the skin barrier, consistent with the symptom of xerosis commonly observed in senile pruritus [5].…”
Section: Skin Barrier Functionsupporting
confidence: 82%
“…In this study, senile pruritus patients had significantly higher TEWL values than control subjects (13.13 ± 4.28 versus 6.71 ± 2.45, p < 0.01; Table 3). These results suggest that senile pruritus is associated with dysfunction of the skin barrier, consistent with the symptom of xerosis commonly observed in senile pruritus [5].…”
Section: Skin Barrier Functionsupporting
confidence: 82%
“…In this study, senile pruritus patients had signi cantly higher TEWL values than control subjects (13.13±4.28 versus 6.71±2.45, p<0.01; Table 3). These results suggest that senile pruritus is associated with dysfunction of the skin barrier, consistent with the symptom of xerosis commonly observed in senile pruritus (5).…”
Section: Skin Barrier Functionsupporting
confidence: 82%
“…Although univariate analysis showed that there was no significant association between patients with and without UDOP, and xerosis, the contribution of xerosis to pruritus should not be overlooked in patients especially with chronic pruritus in the presence of SSLs. While pruritus is a common symptom in the elderly population, xerosis is the most frequent dermatological change leading to pruritus in this group (17).…”
Section: Discussionmentioning
confidence: 99%